Noncitizenism recognising noncitizen capabilities in a world of citizens - Bloom, Tendayi (Routledge studies on challenges, crises and dissent in world politics, 2018)
Noncitizens have always been present in liberal political philosophy. This book is for students and scholars of political philosophy and for those interested in noncitizenship and how it can inform the response of liberal theory, citizenship, global justice, migration studies, political theory and policy work.